Marginal metallic state at a fractional filling of ’8/5’ and ’4/3’ of Landau levels in the GaAs/AlGaAs 2D electron system - R. G. Mani (Nature Portfolio, 2021)
Abstract A metallic state with a vanishing activation gap, at a filling factor $$ν = 8/5$$ ν = 8 / 5 in the untilted specimen with $$n= 2 × 10^{11} cm^{-2}$$ n = 2 × 10 11 c m - 2 , and at $$ν = 4/3$$ ν = 4 / 3 at $$n=1.2 × 10^{11} cm^{-2}$$ n = 1.2 × 10 11 c m - 2 under a $$θ = 66^{0}$$ θ = 66 0 tilted magnetic field, is examined through a microwave photo-excited transport study of the GaAs/AlGaAs 2 dimensional electron system (2DES). The results presented here suggest, remarkably, that at the possible degeneracy point of states with different spin polarization, where the 8/5 or 4/3 FQHE vanish, there occurs a peculiar marginal metallic state that differs qualitatively from a quantum Hall insulating state and the usual quantum Hall metallic state. Such a marginal metallic state occurs most prominently at $$ν =8/5$$ ν = 8 / 5 , and at $$ν =4/3$$ ν = 4 / 3 under tilt as mentioned above, over the interval $$1 \le ν \le 2$$ 1 ≤ ν ≤ 2 , that also includes the $$ν = 3/2$$ ν = 3 / 2 state, which appears perceptibly gapped in the first instance.